Case of a Male Newborn with Incontinentia Pigmenti Initially Misdiagnosed as a Recurrent Skin Infection - Sang Ho Park; Kyung-Hwa Nam; Yo Han Ho (Korean Society of Neonatology, 2020)
Incontinentia pigmenti (IP), also known as Bloch-Sulzberger syndrome, is a rare X-linked dominant disorder that is generally lethal to males and almost always leads to death in utero. This disorder is a genodermatosis with characteristic cutaneous lesions and manifestations affecting the eyes, teeth, hair, and central nervous system. Genodermatosis is a hereditary disease caused by mutations in the nuclear factor-kappa B essential modulator gene mapped to chromosome Xq28. This gene encodes a variety of cytokines and chemokine regulators and is indispensable for protecting cells from tumor necrosis factor-induced apoptosis. Here we describe a case of male newborn with vesiculobullous cutaneous lesions over the left thigh and leg. We first considered the cutaneous lesions a skin infection, as they improved with intravenous antibiotics. However, recurrence and the need for repeated hospitalizations made us consider the differential diagnosis of IP, for which we performed a skin biopsy and chromosome analysis. The histology results were compatible with IP, that is, eosinophilic infiltration in the dermis and epidermis, and individual cell dyskeratinization. The chromosome analysis result was a normal 46, XY karyotype. Here we report the case of a male newborn with IP that manifested as multiple vesiculobullous skin lesions and was initially misdiagnosed as a recurrent skin infection.